Stakeholder dynamics and territorial disputes in nature reserves management: A case of Cwebe community, Eastern Cape, South Africa - James Donald Nyamahono (Interdisciplinary Journal of Rural and Community Studies)
Nature reserves are important ideational spaces where global goals on environmental conservation can be achieved. However, their management is complex and challenging when multiple stakeholders claim ownership and control. This study was centered on this debate and explored stakeholder dynamics and territorial disputes around nature reserves, with a focus on Mhlanganisweni and eLalini Villages situated adjacent to Cwebe Nature Reserve (used interchangeably with 'the Nature Reserve') in South Africa. The aim was to understand the dynamics of the relationship between local communities and the Nature Reserve management, and to investigate how these factors contribute to territorial disputes and their consequences. Qualitative data was collected from women, youth, the elderly, and traditional authorities on one hand, and the management of the Nature Reserve on the other. The study found complex stakeholder relationships among stakeholders, with local communities frequently losing out in territorial disputes. This outcome is evident from the territorial disputes that arise over exclusion in decision-making, natural resource exploitation, and conservation policies within and around the Nature Reserve. The study recommends the implementation of a more inclusive conservation framework that acknowledges the perspectives of multiple stakeholders.